Molecular pathways and diagnosis in malignant mesothelioma: A review of the 14th International Conference of the International Mesothelioma Interest Group. (January 2019) - Chapel, David B.; Churg, Andrew; Santoni-Rugiu, Eric; Tsujimura, Tohru; Hiroshima, Kenzo; Husain, Aliya N.
Highlights: Higher nuclear grade and tumor necrosis predict shorter survival in mesothelioma. Prognostic factors overlap substantially in peritoneal and pleural mesothelioma. Overexpression of MET or EZH2 predicts shorter survival in mesothelioma. MET protein overexpression correlates poorly with MET amplification. HEG1 is a sensitive and specific marker of mesothelial lineage. Abstract: The pathologist plays a central role in the diagnosis and management of malignant mesothelioma, including definitive tissue-based diagnosis in conjunction with clinical and radiographic data; diverse ancillary studies of diagnostic, prognostic, and predictive importance; and research efforts to better define the pathobiology of mesothelioma and develop novel clinical applications. The pivotal role of pathology in care of mesothelioma patients was on display at the recent meeting of the International Mesothelioma Interest Group (iMig) in Ottawa, Canada. This review summarizes the key findings of the "Molecular Pathways and Diagnosis in Malignant Mesothelioma" plenary session, including a large multi-institutional validation of a composite nuclear grading system for pleural mesothelioma, including incorporation of tumor necrosis as an additional independent prognostic factor; the correlation between nuclear grading in small biopsies and paired resection specimens in pleural mesothelioma; a multi-institutional study of important clinical and pathologic prognostic factors in peritoneal mesothelioma; the diagnostic role of HEG1 immunohistochemistry as a highly sensitive and specific marker of mesothelial lineage; the prevalence and diagnostic significance of MET protein overexpression in mesothelioma, as well as the correlation between MET protein overexpression and MET gene amplification; and the prognostic role of EZH2 protein overexpression in mesothelioma, together with data indicating an important pathogenic role for EZH2 in mesothelioma tumorigenesis. Special consideration is given to the convergence of diagnostic, prognostic, and predictive tools and their role in guiding highly personalized patient-centered management, and to the translation of novel research findings to practical techniques for routine pathologic practice.